Pendidikan dan Stratifikasi Sosial Dalam Realitas Universitas Muhammadiyah Makassar - Fathul Fathul Janna; Nurul Asyifah; Nurmi Kahriar; Irmawati Irmawati; Sam'un Mukramin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
God created humans as the noblest beings who were given the gift to be fully responsible for their existence in their surroundings. However, even though humans are given the freedom to be responsible, humans are trapped in the social structure that they have created themselves, so that humans become the horse of the system they created, then there is no longer a balanced structure between humans and their environment and society and culture. In every aspect of society in general, power is a form of embodiment of the problems of social stratification that modern society has. The existence of social stratification can cause an imbalance of rights and obligations that can affect to a certain degree the relations between members of society. Soekanto stated that the emergence of social stratification is caused by the existence of something that is valued in society. Education is basically highly correlated with a person's social status regarding research on the relationship between education and a person's social status has been carried out a lot. Because basically parents who are able will try to send their children to the level of tertiary education even though they have to pay dearly to send their children to school. Even so, basically social stratification will not be avoided. While social mobility is a community movement in activities towards better change. As Horton and Chester in Idi say that: